Development of ICMLS Version 2 (Integrated Communication and Mobile Laboratory Simulator) To Improve 4.0 Century Industry Skills in Vocational Schools - Darmawan, Deni (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The focus of this research was to develop an "ICMLS (Integrated Communication Mobile Laboratory Simulator)" in the form of mobile laboratories innovations for vocational teachers and students of Computer and Network Engineering. This was produced through the development of R & D with support from industrial partners in order to make all teachers and students in Vocational High School, West Java experiences the quality of the product. The prototype developed accommodated all practical activities for class X to XII in one integrated package for server and client functions. This research was conducted for 2 years, and in the first year, 2018, ICMLS version 1.0 was produced and 2.0 will be produced in the second year. This product can improve the competence of Vocational students in Computer and Network Engineering Study Programs to compete in the 4.0 Industrial Revolution Era which is more characterized by Artificial Intelligence and Big Data. This was evident from the increase in the average competency test of students from 85.13 to 85.53 produced from the lowest initial skill average of 77.9 to the highest of 89.4.